Effectiveness of a Modified Pregnancy Support Belt in Reducing Back and Pelvic Pain in Pregnant Women: A Quasi-Experimental Study in South Jakarta - Paisal, Fitrah Ivana; Arifuddin, Hidayanti; Arieska, Risa; Rasumawati, Rasumawati; Vitania, Wiwit; Arifuddin, Adhar (Journal of Health and Nutrition Research, 2025)
Lower back and pelvic pain are common complaints among pregnant women, particularly in the third trimester, due to physiological and hormonal changes. These discomforts significantly impact daily functioning and quality of life. To evaluate the effectiveness of a modified pregnancy support belt in reducing lower back and pelvic pain among pregnant women in the South Jakarta area. This quasi-experimental study involved 60 pregnant women in their third trimester, divided into two groups: an intervention group and a control group. The intervention group used the modified pregnancy support belt, while the control group used a standard pregnancy belt. Pain levels were measured before and after the intervention using the Visual Analogue Scale (VAS). Sociodemographic characteristics, including age, education, occupation, and parity, were also analyzed. Most respondents were aged 20–35 years, housewives, and high school graduates. The mean reduction in VAS scores was 3.1 (95% CI: 2.6–3.6) in the intervention group compared to 2.3 (95% CI: 1.5–3.1) in the control group. Back and pelvic pain were associated with a measurable decrease post-intervention (p < 0.05). The use of a modified pregnancy support belt demonstrated a greater reduction in lower back and pelvic pain compared to a standard belt. Supportive belts should be considered as a non-pharmacological intervention to enhance maternal comfort and well-being during pregnancy.